A fibrosis-informed refinement of the intermediate-risk stratum for statin allocation: a liver-derived hypothesis anchored to the 2026 PREVENT-based guideline framework - Soon Woo Nam (Frontiers in Medicine, 2026)
Statin efficacy is settled; the decisive question is in whom absolute benefit exceeds absolute harm by a margin justifying lifelong therapy. Because proportional risk reduction is approximately constant, absolute benefit scales with baseline risk while the principal harm, incident type 2 diabetes, does not, so a threshold must exist below which treatment is unjustified. The PREVENT equations, published in 2023–2024 and adopted by the 2026 ACC/AHA Multisociety dyslipidemia guideline, lower risk estimates and compress the intermediate band to a 10-year risk of 5% to less than 10%, a large, ambiguous stratum populated by patients with metabolic dysfunction-associated steatotic liver disease (MASLD). MASLD affects two in five adults, causes more cardiovascular than hepatic death, and is untreated in about half of eligible patients owing to a now-discredited fear of hepatotoxicity. Existing reviews establish that statins are safe in MASLD and that its cardiovascular risk is excess and graded, but none translates this into a tool for decision-making at the point of care. I advance a testable hypothesis: the fibrosis-4 (FIB-4) index and liver stiffness measurement should function as formal risk-enhancing modifiers subdividing this stratum. Every term of the upgrade rule is specified quantitatively: a two-threshold FIB-4 structure (rule-out below 1.3, or below 2.0 above age 65; rule-in at 2.67 or above, with 1.3–2.67 resolved by liver stiffness or coronary artery calcium), liver stiffness thresholds of 8 and 12 kPa, an explicit cardiometabolic-criterion list, and a 30-year PREVENT ASCVD risk of 10% or more. The supporting evidence is observational throughout, and I state plainly what is unestablished, namely that these markers add prognostic information beyond PREVENT and coronary artery calcium; fibrosis is framed as a marker of cumulative cardiometabolic injury, not a causal mediator. I situate the framework alongside resmetirom, incretin therapy, and bempedoic acid, define the fibrosis boundary beyond which competing liver-related mortality invalidates it, and specify a competing-risks validation design aligned to the PREVENT total cardiovascular disease endpoint, externally validated in East Asian and lean-MASLD cohorts. The contribution is a fully specified, falsifiable decision architecture for the stratum where guidelines leave clinicians most uncertain.